Rancang Bangun Alat Pencetak Briket Hidrolik dengan Sistem Gerak Rel - Diah Mahmuda (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
This study aims to design a hydraulic briquette press with a rail system to produce briquettes from coconut shell waste that is simple and easy to operate. Starting from designing the foundation (rail system), briquette tube table and piston pressing plate, to becoming a pressing tool using CAD software. The foundation was designed using square plate steel with size of 340 mm x 220 mm. The plate thickness of 4 mm and distance of 2 rails of 90 mm. The pressing tube plate consists of 2 tables which has 8 print tubes with a diameter of 22 mm and height 70 mm. The pressing piston plate uses a bolt connection so the piston can be set in line with the printing tube hole when the briquette press is operated. As a result, a hydraulic press with a table movement system in the form of a rail system was successfully built to make briquettes made from coconut shell charcoal with a capacity of 6.24 kg per hour. In one process, this tool produces 16 cylindrical briquettes with a diameter of 22 mm and a length of 50 mm.